Energy use and rural poverty: Empirical evidence from potato farmers in north China - Li, Zihan; Gong, Yazhen; Chen, Kevin Z. (International Food Policy Research Institute, 2016)
Rising energy expenditures due to more intensive use of energy in modern agriculture and increasing energy prices may affect rural households’ agricultural incomes, particularly the incomes of the rural poor in developing countries. However, the exact link between energy costs and income among the rural poor needs further empirical investigation. This paper aims to gain a deeper understanding of the relationship between energy use and family income, using household-level panel data collected from 500 potato farmers in a poor region of Northern China, where eliminating poverty by 2020 is now the top government priority. The findings indicate that potato plays an important role in the surveyed families’ incomes, and the energy costs of potato production have a significant negative relationship with family income. However, the significance of the negative relationship is robust only for farmers with low economic standing, such as those living below the poverty line or just above it. Energy costs also have a significant negative relationship with the family incomes of those cultivating a certain size of potato-sown area, but this relationship becomes insignificant when farmers have too small of a potato-sown area. These findings indicate that in general, reducing energy costs helps the poor increase their income but is not necessarily helpful to those with high economic standing or a relatively small potato-sown area. If rural development policies are to support poverty reduction and energy savings (at least in major potato production regions), interventions aimed at energy cost reduction may be effective only for the poor whose family income depends, to a relatively high degree, on potato production.